Evaluation of demographic and neuro-ophthalmologic findings of patients with multiple sclerosis - Orman, Gözde; Sungur, Gülten (International ophthalmology, 2024)
Purpose The study aims to investigate the demographic and neuroophthalmologic features of patients with multiple sclerosis (MS). Methods This retrospective study investigated 270 eyes of 135 patients with MS. All subjects underwent a full ophthalmological examination. Results The study investigated 270 eyes of 135 patients with MS. The patients included 102 (74.8%) females and 34 (25.2%) males. The mean age at the time of diagnosis of MS was 29.9 ± 9.6 years. The mean follow-up period was 6.7 ± 10.9 months. Initial symptoms of MS at presentation included optic neuritis (ON) in 42 patients (15.6%), numbness of hands and feet in 20 patients (7.4%) and diplopia in 11 patients (4.1%). Additional diseases were observed in 29 patients (21.5%) and autoimmune diseases were observed in 11 patients (8.1%). Thirteen patients (9.62%) had relatives with MS; the relatives of five patients were first-degree relatives and the relatives of the remaining eight patients were second-degree relatives. Table 2 summarizes the additional systemic and ocular diseases and family history data. During MS, 72 patients (53.4%) were diagnosed with ON. ON was bilateral in 49 patients (68%) and unilateral in 23 patients (32%). Retrobulbar ON was observed in 77 eyes (81.6%) and papillitis was observed in 18 eyes (18.4%). Disorders of efferent visual pathway function were found in 43 patients (30.4%). Conclusion Visual impairments are significant in patients with MS. Although ON is the most prevalent symptom of MS, it is important to keep in mind that damage to the efferent visual system can be observed.